Method for accelerating degradation of waste polyester

By using a system of organic alcohol, organic alkali and photodegradation catalyst for light and heating treatment under low temperature conditions, the problems of low degradation efficiency of polyester and low product purity in the prior art were successfully solved, and efficient and environmentally friendly polyester degradation and high purity production of diol terephthalate were achieved.

CN119841728AActive Publication Date: 2025-04-18YANTAI TAYHO ADVANCED MATERIALS RES INST CO LTD

Patent Information

Application Number
CN202510336067.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-21
Publication Date
2025-04-18
Estimated Expiration
2045-03-21

AI Technical Summary

Technical Problem

The prior art requires high temperature and high pressure conditions when degrading waste polyester, and uses strong acids, strong alkalis and heavy metal catalysts, which lead to equipment corrosion and environmental pollution, and has low degradation efficiency and low product purity.

Method used

The pulverized polyester material is subjected to light and heat treatment in a system of organic alcohol, organic alkali and photodegradation catalyst by adopting a fast low temperature degradation method, and diol terephthalate is obtained by constant temperature solid-liquid separation, cooling crystallization, washing and drying.

Benefits of technology

It achieves efficient degradation of polyester at low temperatures, reduces energy consumption, improves yield and product purity, reaching more than 99%, and avoids secondary pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119841728A_ABST
    Figure CN119841728A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of recycling of waste textiles, in particular to a method for accelerating degradation of waste polyester, which comprises the following steps: S1, adding crushed polyester materials into organic alcohol, and then adding organic alkali and a photodegradation catalyst to obtain a degradation system; and S2, carrying out a degradation reaction in the degradation system under illumination and heating conditions, and after the reaction is finished, carrying out constant-temperature solid-liquid separation, cooling crystallization, washing and drying to obtain the terephthalic acid glycol ester. The photodegradation catalyst is at least one of nano ZnO and nano TiO2. According to the method disclosed by the invention, low-temperature and rapid degradation can be realized to obtain the terephthalic acid glycol ester, the energy consumption of polyester degradation is effectively reduced, the yield of polyester recovery is improved, and the recycling of polyester fabrics is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for accelerating the degradation of waste polyester, and belongs to the technical field of recycling and reusing waste textiles. Background Art

[0002] Saving resources and protecting the environment are the problems that the world needs to solve together today, especially in the chemical fiber industry, which is highly dependent on petroleum resources and has a large volume and wide range. Among them, polyester is one of the most popular fiber materials in the world. In addition to being used as a textile fiber, polyester is often blended with other fibers. The blended fabric can not only retain the excellent mechanical properties of polyester, but also increase the performance of other fabrics, further improving the use scenarios of the fabric. With the improvement of people's living consumption level, the use cycle of textiles has been greatly shortened, the demand for textile fibers has increased rapidly, and various discarded textiles have continued to increase every year in the world, while waste textiles are rarely recycled and are mostly directly buried or incinerated. Since synthetic fiber textiles such as polyester are not easy to degrade, they are extremely harmful to the soil environment after being buried. In addition, textiles containing synthetic fibers will produce a large amount of toxic gases during the combustion process, causing air pollution. Therefore, the recycling and reuse of waste textiles, especially the recycling and reuse of polyester, can not only alleviate the current situation of resource shortage in the chemical fiber industry, but also reduce the pollution caused by chemical fiber textiles (such as polyester, etc.) to the environment, which has great economic and social benefits.

[0003] At present, the recycling technology of polyester in waste textiles is mainly based on chemical depolymerization of polyester. However, the depolymerization process of polyester fibers is often accompanied by harsh reaction conditions. It is generally necessary to carry out under high temperature and high pressure conditions, and strong acids, strong bases, heavy metals, etc. are also required as catalysts, which can easily cause corrosion to equipment, and excessive use of heavy metals will seriously harm the environment. In addition, since the depolymerization conditions of hydrolysis and alcoholysis technology are extremely harsh, for blended textiles, other blended fibers will also experience corresponding degradation. In order to avoid the impact of the degradation of these non-polyester components, it is particularly important to develop catalysts with mild reaction conditions, high catalytic activity, and improve the degradation method.

[0004] In addition, the patent application with publication number CN117964474A discloses a neutral hydrolysis method for waste polyester without waste liquid discharge, firstly, ethylene glycol is used to partially depolymerize PET in waste polyester textiles, impurities are removed, and purified partially depolymerized PET is obtained, and then hydrolyzed to produce terephthalic acid, ethylene glycol and water. After decomposing polyester by this method, small molecular terephthalic acid and ethylene glycol are obtained, and the application rate in polymer materials is relatively low. If a polyester degradation method for obtaining terephthalic acid glycol ester can be developed, it will be of great significance, because terephthalic acid glycol ester can be widely used in the fields of fibers, plastic bottles, films, etc., and the utilization rate is higher. Summary of the invention

[0005] The present invention aims at the deficiencies in the prior art and provides a method for accelerating the degradation of waste polyester. The method adopted by the present invention can achieve low-temperature and rapid degradation to obtain terephthalate glycol ester, effectively reducing the energy consumption of polyester degradation, improving the yield of polyester recovery, and realizing the recycling and utilization of polyester fabrics.

[0006] The technical solution of the present invention to solve the above technical problems is as follows: A method for accelerating the degradation of waste polyester, the method for accelerating the degradation of waste polyester comprising: S1, adding the crushed polyester material into an organic alcohol, and then adding an organic base and a photodegradation catalyst to obtain a degradation system; S2. Under the conditions of light and heating, a degradation reaction is carried out in the degradation system. After the reaction is completed, terephthalic acid glycol ester is obtained through constant temperature solid-liquid separation, cooling crystallization, washing and drying.

[0007] Furthermore, the organic alcohol is methanol.

[0008] Furthermore, the organic base is at least one of 1,5-diazabicyclo[4.3.0]-5-nonene, 1,8-diazabicyclo[5.4.0]undec-7-ene, 1,8-diazabicyclo[5.4.0]undec-7-ene, and 1,1,3,3-tetramethylguanidine.

[0009] Furthermore, the photodegradation catalyst is at least one of nano ZnO and nano TiO2.

[0010] Furthermore, in step S1, the mass ratio of the polyester material to the organic alcohol is 1:(1-2); the amount of the organic base added is 0.1%-1.0% of the mass of the polyester material; and the amount of the photodegradation catalyst added is 0.03%-0.06% of the mass of the polyester material.

[0011] Furthermore, in step S2, the illumination wavelength is 256-365nm, and the illumination power is 20-150W.

[0012] Furthermore, in step S2, the heating temperature is 60-90°C; and the reaction time is 30min-120min.

[0013] Furthermore, in step S2, the solid separated from the solid-liquid separation at constant temperature is added to the organic alcohol again, and the organic base is added to perform the degradation reaction again.

[0014] Furthermore, in step S2, the solvent used for washing is methanol; The drying temperature during drying is 50-80°C and the drying time is 4 hours.

[0015] Furthermore, in step S2, the filtrate obtained during the cooling and crystallization is subjected to distillation separation to obtain methanol, ethylene glycol and an organic base.

[0016] The beneficial effects of the present invention are: 1. The method for accelerating the degradation of waste polyester of the present invention is advanced and has a simple process; the raw materials used can be recycled, which can reduce costs and will not cause secondary pollution.

[0017] 2. The present invention adopts an organic base (such as 1,5-diazabicyclo[4.3.0]-5-nonene, 1,8-diazabicyclo[5.4.0]undec-7-ene, 1,8-diazabicyclo[5.4.0]undec-7-ene, 1,1,3,3-tetramethylguanidine) as a catalyst for thermal alcoholysis and nanoparticles (such as nano ZnO, nano TiO2) as a catalyst for photocatalytic degradation. The molecules that are not completely degraded during the degradation process are continuously degraded, the degradation degree of polyester is improved, and the purity of the terephthalic acid diol ester product is improved, so that energy consumption can be reduced and the purity of the terephthalic acid diol ester product can be improved.

[0018] 3. The present invention adopts a cooling crystallization precipitation method to purify the final terephthalic acid glycol ester product, which is simple to operate and the purity of the obtained terephthalic acid glycol ester product can reach more than 99%. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 is the liquid phase spectrum of terephthalate obtained in Example 1; Figure 2 This is the infrared spectrum of the terephthalate obtained in Example 1. DETAILED DESCRIPTION

[0020] The specific implementation of the present invention is described in detail below. The present invention can be implemented in many other ways than those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed.

[0021] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used are only for describing specific embodiments and are not intended to limit the present invention.

[0022] A method for accelerating the degradation of waste polyester, the method for accelerating the degradation of waste polyester comprising: S1, adding the crushed polyester material into an organic alcohol, and then adding an organic base and a photodegradation catalyst to obtain a degradation system; S2. Under the conditions of light and heating, a degradation reaction is carried out in the degradation system. After the reaction is completed, terephthalic acid glycol ester is obtained through constant temperature solid-liquid separation, cooling crystallization, washing and drying.

[0023] Specifically, the organic alcohol is methanol.

[0024] Specifically, the organic base is at least one of 1,5-diazabicyclo[4.3.0]-5-nonene (DBN), 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU), 1,8-diazabicyclo[5.4.0]undec-7-ene (TBD), and 1,1,3,3-tetramethylguanidine (TMG).

[0025] Specifically, the photodegradation catalyst is at least one of nano ZnO and nano TiO2.

[0026] Specifically, in step S1, the mass ratio of the polyester material to the organic alcohol is 1:(1-2); the amount of the organic base added is 0.1%-1.0% of the mass of the polyester material; and the amount of the photodegradation catalyst added is 0.03%-0.06% of the mass of the polyester material.

[0027] More preferably, the mass ratio of the organic base to the photodegradation catalyst is not less than 2.0.

[0028] Specifically, in step S2, the illumination wavelength is 256-365nm, and the illumination power is 20-150W.

[0029] Specifically, in step S2, the heating temperature is 60-90°C; and the reaction time is 30min-120min.

[0030] Specifically, in step S2, the solid separated by constant temperature solid-liquid separation is added to the organic alcohol again, and the organic base is added to perform degradation reaction again. The solid obtained by constant temperature solid-liquid separation is the photodegradation catalyst and the polyester that is not completely degraded.

[0031] Specifically, in step S2, the cooling temperature for cooling crystallization is 5-25°C, and the cooling time is 2h-5h; The solvent used in the washing is methanol; The drying temperature during drying is 50-80°C and the drying time is 4 hours.

[0032] Specifically, in step S2, the filtrate obtained during the cooling and crystallization is subjected to rectification and separation to obtain methanol, ethylene glycol and an organic base. Methanol and the organic base can be recycled again. Ethylene glycol can be used as an industrial raw material.

[0033] More specifically, in step S1, the polyester material is polyester waste silk, waste cloth and clothing scraps. When the polyester material is polyester waste cloth, a pulverizer is used to pulverize the polyester waste cloth to obtain a size of about 10×3 mm. 2 The rags undergo degradation reactions.

[0034] Example 1 The broken polyester rags were added to methanol, the mass ratio of polyester rags to methanol was 1:1.5, and then 0.03% of the mass of the polyester rags was added as a photodegradation catalyst nano zinc oxide and 0.1% of the mass of the polyester rags was added as 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU). Under the condition of heating at 65°C, 150W ultraviolet light was used for photodepolymerization. The reaction was stopped after 120 minutes, and the undegraded polyester rags and the catalyst were separated by hot filtration. The degraded filtrate was cooled and crystallized, wherein the cooling crystallization temperature was 5°C and the cooling time was 2h. The solid precipitated by cooling was filtered, separated, washed, and dried to obtain the final product of terephthalic acid glycol ester.

[0035] like Figure 1 and 2 The purity of terephthalate was determined by liquid chromatography and infrared chromatography. The conversion rate of the product was determined by measuring the mass of the final product. The purity of the final terephthalate product was 99%, and the degradation rate of polyester was 95%.

[0036] Example 2 The broken polyester rags were added to methanol, the mass ratio of polyester rags to methanol was 1:1.5, and then 0.03% of the mass of polyester rags was added as a photodegradation catalyst nano zinc oxide and 0.1% of the mass of polyester rags was added. Under the condition of heating at 65°C, 150W ultraviolet light was used for photodepolymerization. The reaction was stopped after 120 minutes, and the undegraded polyester rags and catalyst were separated by hot filtration. The degraded filtrate was cooled and crystallized, wherein the cooling crystallization temperature was 10°C and the cooling time was 2h. The solid precipitated by cooling was filtered, separated, washed, and dried to obtain the final product, diol terephthalate. The purity of the final diol terephthalate product was 99%, and the degradation rate of polyester was 92%.

[0037] Example 3 The broken polyester rags were added to methanol, the mass ratio of polyester rags to methanol was 1:1.5, and then 0.03% of the mass of polyester rags was added as a photodegradation catalyst nano zinc oxide and 0.1% of the mass of polyester rags was added as 1,8-diazabicyclo[5.4.0]undec-7-ene (TBD). Under the condition of heating at 65°C, 150W ultraviolet light was used for photodepolymerization. The reaction was stopped after 120 minutes, and the undegraded polyester rags and catalyst were separated by hot filtration. The degraded filtrate was cooled and crystallized, wherein the cooling crystallization temperature was 5°C and the cooling time was 2h. The solid precipitated by cooling was filtered, separated, washed, and dried to obtain the final product of terephthalic acid glycol ester. The purity of the final product was 99%, and the degradation rate of polyester was 91%.

[0038] Example 4 The broken polyester rags were added to methanol, the mass ratio of polyester rags to methanol was 1:1.5, and then 0.03% of the mass of polyester rags was added as a photodegradation catalyst nano zinc oxide and 0.1% of the mass of polyester rags as 1,1,3,3-tetramethylguanidine (TMG). Under the condition of heating at 65°C, 150W ultraviolet light was used for photodepolymerization. The reaction was stopped after 120 minutes, and the undegraded polyester rags and catalyst were separated by hot filtration. The degraded filtrate was cooled and crystallized, wherein the cooling crystallization temperature was 25°C and the cooling time was 5h. The solid precipitated by cooling was filtered, separated, washed, and dried to obtain the final product of terephthalic acid glycol ester. The purity of the final product was 99%, and the degradation rate of polyester was 92%.

[0039] Example 5 The broken polyester rags were added to methanol, the mass ratio of polyester rags to methanol was 1:1.5, and then 0.03% of the mass of the polyester rags was added as a photodegradation catalyst nano-titanium oxide and 0.1% of the mass of the polyester rags was added as 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU). Under the condition of heating at 65°C, 150W ultraviolet light was used for photodepolymerization. The reaction was stopped after 120 minutes, and the undegraded polyester rags and the catalyst were separated by hot filtration. The degraded filtrate was cooled and crystallized, wherein the cooling crystallization temperature was 5°C and the cooling time was 3h. The solid precipitated by cooling was filtered, separated, washed, and dried to obtain the final product, diol terephthalate. The purity of the final product was 99%, and the degradation rate of polyester was 95%.

[0040] Example 6 The degradation of polyester was carried out in the same manner as in Example 1, except that the proportion of the photodegradation catalyst in Example 6 was 0.05%. The purity of the final product was 99%, and the degradation rate of polyester was 94%.

[0041] Example 7 The degradation of polyester was carried out in the same manner as in Example 1, except that the proportion of the organic base catalyst in Example 7 was 0.4%. The purity of the final product was 99%, and the degradation rate of polyester was 96%.

[0042] Example 8 The degradation of polyester was carried out in the same manner as in Example 1, except that the proportion of the organic base catalyst in Example 8 was 0.8%. The purity of the final product was 99%, and the degradation rate of polyester was 97%.

[0043] Example 9 The degradation of polyester was carried out in the same manner as in Example 1, except that the proportion of the organic base catalyst in Example 9 was 1%. The purity of the final product was 99%, and the degradation rate of polyester was 97%.

[0044] Example 10 The broken polyester rags were added to methanol, the mass ratio of polyester rags to methanol was 1:1, and then 0.04% of the mass of polyester rags was added as a photodegradation catalyst nano zinc oxide and 0.4% of the mass of polyester rags as 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU). Under the condition of heating at 60°C, 20W ultraviolet light was used for photodepolymerization. The reaction was stopped after 120 minutes, and the undegraded polyester rags and catalyst were separated by hot filtration. The degraded filtrate was cooled and crystallized, wherein the cooling crystallization temperature was 5°C and the cooling time was 2h. The solid precipitated by cooling was filtered, separated, washed, and dried to obtain the final product, diol terephthalate. The purity of the final diol terephthalate product was 99%, and the degradation rate of polyester was 94%.

[0045] Embodiment 11 The broken polyester rags were added to methanol, the mass ratio of polyester rags to methanol was 1:2, and then 0.05% of the mass of polyester rags was added as a photodegradation catalyst nano zinc oxide and 1.0% of the mass of polyester rags was added. Under the condition of heating at 90°C, 100W ultraviolet light was used for photodepolymerization. The reaction was stopped after 30 minutes, and the undegraded polyester rags and catalyst were separated by hot filtration. The degraded filtrate was cooled and crystallized, wherein the cooling crystallization temperature was 5°C and the cooling time was 4h. The solid precipitated by cooling was filtered, separated, washed, and dried to obtain the final product, diol terephthalate. The purity of the final diol terephthalate product was 99%, and the degradation rate of polyester was 94%.

[0046] Example 12 The degradation of polyester was carried out in the same manner as in Example 1, except that the proportion of the photodegradation catalyst in Example 6 was 0.06%. The purity of the final product was 99%, and the degradation rate of polyester was 97%.

[0047] It can be seen from the experimental results of the above examples 1 to 12 that the degradation rate of polyester can be accelerated by using the method of the present invention. Under appropriate degradation conditions, the degradation of waste polyester can be completely achieved within two hours, the degradation rate of polyester can even reach more than 97%, and the purity of terephthalic acid glycol ester is not less than 99%. The method for preparing terephthalic acid glycol ester by degrading waste polyester provided by the present invention can, to a certain extent, make up for the problems of high energy consumption, low degradation rate and low purity of the product in the prior art of polyester degradation. In addition, from the data comparison of Example 1, Example 6 and Example 12, it can be seen that when the mass ratio of the organic base to the photodegradation catalyst is ≥2.0, it is more conducive to the efficient degradation of polyester, because the appropriate proportion of the organic base and the photodegradation catalyst can form a coordination relationship, so that the photodegradation catalyst is evenly embedded in the organic base, which is more conducive to the efficient degradation of polyester in a suspended state in the degradation system. When the amount of the photodegradation catalyst is too much, the nano-scale photodegradation catalyst is easy to agglomerate in the degradation system, which ultimately affects the degradation effect. Therefore, the reasonable combination of the organic base and the photodegradation catalyst is more conducive to the efficient degradation of polyester.

[0048] Comparative Example 1 The polyester was degraded by the same method as in Example 1, except that no ultraviolet irradiation was performed in this comparative example 1. The specific preparation process is as follows: The broken polyester rags were added to methanol, the mass ratio of polyester rags to methanol was 1:1.5, and then 0.03% of the mass of polyester rags was added as a photodegradation catalyst nano zinc oxide and 0.1% of the mass of polyester rags was added as 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU). The reaction was carried out under heating conditions of 65°C, and the reaction was stopped after 120 minutes. The undegraded polyester rags and the catalyst were separated by hot filtration, and the degraded filtrate was cooled and crystallized, wherein the cooling crystallization temperature was 5°C and the cooling time was 2h. The solid precipitated by cooling was filtered, separated, washed, and dried to obtain the final product of terephthalic acid glycol ester. The purity of the final product was 97%, and the degradation rate of polyester was 88%.

[0049] Comparative Example 2 The polyester was degraded by the same method as in Example 1, except that no heating was performed during the degradation reaction in Comparative Example 2. The specific preparation process is as follows: The broken polyester rags were added to methanol, the mass ratio of polyester rags to methanol was 1:1.5, and then 0.03% of the mass of polyester rags was added as a photodegradation catalyst nano zinc oxide and 0.1% of the mass of polyester rags was added as 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU). 150W ultraviolet light was used for photodepolymerization. The reaction was stopped after 120 minutes of reaction, and the undegraded polyester rags and the catalyst were separated by constant temperature filtration. The degraded filtrate was cooled and crystallized, wherein the cooling crystallization temperature was 5°C and the cooling time was 2h. The solid precipitated by cooling was filtered, separated, washed, and dried to obtain the final product, diol terephthalate. The conversion rate of the product was determined by measuring the mass of the final product. The purity of the final diol terephthalate product was 10%, and the degradation rate of polyester was 25%.

[0050] From the comparison of the experimental results of Comparative Example 1, Comparative Example 2 and Example 1, it can be seen that in the degradation process of polyester, simultaneous heating and illumination are more conducive to achieving efficient degradation of polyester, and the purity of terephthalate glycol ester can reach 99%. Because organic bases can quickly degrade polyester polymers into low molecular weight polymers, the introduction of photocatalysts can quickly degrade low molecular weight polymers into small molecular monomers under the synergistic effect of organic bases under the action of ultraviolet light, thereby improving the degradation rate and purity.

[0051] Comparative Example 3 The degradation of polyester was carried out in the same manner as in Example 1, except that the amount of the photodegradation catalyst was reduced in Comparative Example 3, and the amount of the photodegradation catalyst in Comparative Example 3 was 0.01% of the mass of the polyester rags. The purity of the final terephthalate glycol ester product was 98%, and the degradation rate of polyester was 90%.

[0052] From the comparison of the experimental data of Example 1 and Comparative Example 1, it can be seen that if the amount of the photodegradation catalyst is reduced, the depolymerization efficiency is reduced in the subsequent depolymerization process of the low molecular weight polyester, resulting in a reduced degradation conversion rate.

[0053] Comparative Example 4 The degradation of polyester was carried out in the same manner as in Example 1, except that the amount of organic base used in this comparative example 4 was reduced, and the amount of organic base used in this comparative example 4 was 0.05% of the mass of the polyester rags. The purity of the final terephthalate glycol ester product was 96%, and the degradation rate of polyester was 81%.

[0054] From the comparison of the experimental data of Example 1 and Comparative Example 2, it can be seen that if the amount of organic base is reduced, the amount of polyester degraded into low molecular weight polyester is reduced, resulting in a lower conversion rate. In addition, the photodegradation catalyst and the organic base form a coordinated relationship to achieve efficient degradation of polyester. If the mass ratio of the organic base to the photodegradation catalyst is less than 2, the efficiency of oligomer degradation into small molecules is reduced, resulting in a lower purity and conversion rate of the final terephthalate glycol ester.

[0055] Comparative Example 5 The degradation of polyester was carried out in the same manner as in Example 1, except that the reaction temperature was increased in Comparative Example 5, and the reaction temperature was 120° C. The purity of the final terephthalate diol product was 98%, and the degradation rate of polyester was 99%.

[0056] From the comparison of the experimental data of Example 1 and Comparative Example 5, it can be seen that if the reaction temperature is increased, the conversion rate of polyester is increased, but the purity of the monomer of the degraded polyester will be significantly reduced, mainly because under the action of high temperature, the organic base can effectively degrade the polyester, and the photoinitiator can continue to decompose the degraded monomer, thereby inducing side reactions and reducing the purity of the depolymerized monomer. Therefore, the combination of organic base and photoinitiator can effectively achieve the degradation of polyester under the condition of lower energy consumption, and in addition, it can improve the purity of the degraded monomer and achieve efficient recovery of polyester.

[0057] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are exhaustively listed. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0058] For those skilled in the art, several modifications and improvements may be made without departing from the concept of the present invention, all of which belong to the protection scope of the present invention. The protection scope of the present invention shall be based on the attached claims.

Claims

1. A method for accelerating the degradation of waste polyester, characterized in that: The method for accelerating the degradation of waste polyester is: S1, adding the crushed polyester material into an organic alcohol, and then adding an organic base and a photodegradation catalyst to obtain a degradation system; S2. Under light and heating conditions, a degradation reaction is carried out in the degradation system. After the reaction is completed, terephthalic acid glycol ester is obtained through constant temperature solid-liquid separation, cooling crystallization, washing and drying.

2. A method for accelerating the degradation of waste polyester according to claim 1, characterized in that: The organic alcohol is methanol.

3. The method for accelerating the degradation of waste polyester according to claim 1, characterized in that: The organic base is at least one of 1,5-diazabicyclo[4.3.0]-5-nonene, 1,8-diazabicyclo[5.4.0]undec-7-ene, 1,8-diazabicyclo[5.4.0]undec-7-ene and 1,1,3,3-tetramethylguanidine.

4. The method for accelerating the degradation of waste polyester according to claim 1, characterized in that: The photodegradation catalyst is at least one of nano ZnO and nano TiO2.

5. The method for accelerating the degradation of waste polyester according to claim 1, characterized in that: In step S1, the mass ratio of the polyester material to the organic alcohol is 1:(1-2); the amount of the organic base added is 0.1%-1.0% of the mass of the polyester material; and the amount of the photodegradation catalyst added is 0.03%-0.06% of the mass of the polyester material.

6. The method for accelerating the degradation of waste polyester according to claim 1, characterized in that: In step S2, the illumination wavelength is 256-365nm, and the illumination power is 20-150W.

7. The method for accelerating the degradation of waste polyester according to claim 1, characterized in that: In step S2, the heating temperature is 60-90°C; and the reaction time is 30 min-120 min.

8. The method for accelerating the degradation of waste polyester according to claim 1, characterized in that: In step S2, the solid separated from the solid-liquid separation at constant temperature is added to the organic alcohol again, and the organic base is added to perform degradation reaction again.

9. The method for accelerating the degradation of waste polyester according to claim 1, characterized in that: In step S2, the solvent used for washing is methanol; The drying temperature during drying is 50-80°C and the drying time is 4 hours.

10. The method for accelerating the degradation of waste polyester according to claim 1, characterized in that: In step S2, the filtrate obtained during the cooling and crystallization is subjected to distillation separation to obtain methanol, ethylene glycol and an organic base.

Citation Information

Patent Citations

  • Recycling method for depolymerization of waste terylene and mild selective depolymerization of blended textiles of waste terylene

    CN116425621A

  • Neutral hydrolysis method for waste polyester without waste liquid discharge

    CN117964474A

  • Waste polyester degradation and decoloration integrated catalyst as well as preparation method and application thereof

    CN118320857A

  • The porous ultra-soft ultra-fine denier polyester fiber and its preparation method

    US20190185616A1

  • The high-uniformity coloured polyester industrial yarn

    US20200199788A1

Cited By

  • Method for accelerating degradation of waste polyester

    WO2026194116A1